Robust H∞ attitude tracking control of a quadrotor UAV on SO(3) via variation-based linearization and interval matrix approach. (April 2019) - Wang, Haibo; Li, Zheng; Xiong, Hongyun; Nian, Xiaohong
Abstract: This paper deals with the attitude tracking control of quadrotor unmanned aerial vehicles (UAV) with uncertainties and external disturbances. The control system is expressed on the special orthogonal group, SO(3), to avoid singularities and ambiguities associated with Euler angles and quaternions respectively. It is also the basis for achieving large angle tracking and complex UAV maneuver. Meanwhile, it greatly reducing the complexity of the controller design via variation-based linearization. And the approach of interval matrix is introduced to solve problems of controller online calculation and reduced control accuracy caused by uncertain parameters in model. The proposed robust H ∞ control system can exponential asymptotically follow a desired attitude trajectory in the presence of unstructured bounded disturbances. Finally, several simulation results are provided to validate the effectiveness, advantages and robustness of the proposed method. Highlights: Take disturbances into consideration and put forward a variation-based linearized attitude error system for quadrotor UAV on SO(3). The interval matrix approach is introduced to describe the parameters changing within a certain range, including time-varying parameters and uncertain parameters. The robust H ∞ attitude tracking control scheme for quadrotor on SO(3) is proposed. The LMI exponential stability sufficient conditions are derived. Simulations are done to demonstrate the effectiveness, advantages and robustness when implementing large angle flip and complex flight maneuvers.